Rapid Accurate and Accurate Medical Services System Innovation in Bangka Regency Depati Bahrin Hospital - Herman Yaarozatulo Harefa (Inovbook Publications, 2021)
Depati Bahrin Hospital experiencing an death rate increased from year to year, seen in 2015 the death rate in Depati Bahrin Hospital have 348 people, while in 2016 amounted to 384 inhabitants. This is what lies behind the need for investment to reduce the mortality rate. This innovation makes the application of a fast service system medical accurate and precise. The method used is descriptive research with qualitative analysis application is proven to be effective to reduce death rate, in 2017 the death rate in Depati Bahrin hospital down to 308 people. It is hoped that in the future this application can be more developed and useful for mankind.